Changes in somatosensory perception induced by trigeminal injury after maxillofacial surgical procedures = Cambios en la percepción somatosensorial inducidos por lesiones trigeminales causadas por procedimientos quirúrgicos maxilofaciales - Luna Velazquez, Mariana Irais
Evidence has been reported that shows that somatosensory perception can be altered by a trigeminal injury resulting from maxillofacial surgical procedures. However, the surgical procedures that most frequently cause trigeminal lesions and the risk factors are unknown. In the same way, there is little information on what has been determined in preclinical models of trigeminal injury. This article integrates relevant information on trigeminal injury from both clinical findings and primary basic science studies. This review shows that the age and complexity of surgical procedures are essential to induce orofacial sensory alterations.